2004
DOI: 10.1007/s00277-004-0959-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of red cell autoantibodies in consecutive DAT-positive patients with relation to in vivo haemolysis

Abstract: The clinical symptoms of patients with autoimmune haemolytic anaemia (AIHA) may range from no symptoms at all to severe haemolysis with life-threatening anaemia. The aim of the present study was to characterize the autoantibodies serologically and to evaluate their activity in vitro in monocyte monolayer assay (MMA) in consecutive direct antiglobulin test (DAT)-positive patients from a haematological department. We also aimed to evaluate the monocyte production of cytokines in vitro and relate all findings to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…Data from erythrophagocytosis tests are generally strongly correlated with the severity of AIHA involving IgG. 28 Our results differed somewhat from those of a previous study reporting moderate phagocytosis in a case of wAIHA with pure IgA. 14 This discrepancy was not due to the use of monocytes from healthy donors in our study, as similar negative results were obtained during the first few days of the follow-up, in coculture experiments with monocytes and sensitized RBCs obtained from fresh blood samples of the patient (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Data from erythrophagocytosis tests are generally strongly correlated with the severity of AIHA involving IgG. 28 Our results differed somewhat from those of a previous study reporting moderate phagocytosis in a case of wAIHA with pure IgA. 14 This discrepancy was not due to the use of monocytes from healthy donors in our study, as similar negative results were obtained during the first few days of the follow-up, in coculture experiments with monocytes and sensitized RBCs obtained from fresh blood samples of the patient (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Therefore, we found it relevant to establish the role of EndoS regarding the in vitro response of monocytes exposed to sensitized RBCs by measuring the release of IL-8. Thus, THP-1 cells and monocytes were incubated with anti-D-sensitized RBCs, and the secretion of IL-8 was measured using ELISA.…”
Section: Endos Inhibits Il-8 Secretion From Monocytes Induced By Sensmentioning
confidence: 99%
“…1,5 It has been recommended that compatible blood must be transfused to AIHA patients carrying RBC-specific autoantibodies; however, some authors ignore the specificity of the autoantibody because some reports have not demonstrated significant differences in the survival of antigen-specific compatible RBCs used for transfusion, or have shown that the benefit was minimal. 1,2,17,18 Patients with CAIHA present positive DAT result with anti-C3 or anti-(C3+IgG) reagents but negative with antiIgG reagent. Table 2 summarizes the immunohematological findings in patients with various types of AIHA.…”
Section: Barros Et Almentioning
confidence: 99%
“…These symptoms generally occur in patients with very profound anemia showing hemoglobin levels below 5 g/dL (Table 4). 1,6,17,18,28,34 In mild or moderate anemias (Hb>8 g/ dL) RBC transfusion is rarely necessary or desirable, as symptoms generally are controlled with appropriated therapy. For patients showing hemoglobin level between 5 and 8 g/dL the clinical decision for transfusion is more difficult.…”
Section: Indications For Transfusion In Aihamentioning
confidence: 99%
See 1 more Smart Citation